PENGARUH KARAKTERISTIK INDIVIDU DAN OCB (ORGANIZATIONAL CITIZENSHIP BEHAVIOR) TERHADAP KINERJA KARYAWAN PT BUMI SIAK PUSAKO KOTA PEKANBARU - Aini, Adilah Qurrotu; Hendriani, Susi; Pramadewi, Arwinence (Universitas Bina Taruna Gorontalo, 2025)
Human resources are the main key to achieving organizational goals, and they are very important in this regard. PT Bumi Siak Pusako is one of the companies that conducts an employee performance assessment. The assessment of managerial employees' work found that the results did not align with the company's targets.This study aims to determine the influence of individual characteristics and Organizational Citizenship Behavior (OCB) on employee performance at PT Bumi Siak Pusako in Pekanbaru City. This research employs a quantitative method with a descriptive approach. Data were collected through questionnaires distributed to the entire population of 119 respondents using a saturated sampling technique. Data analysis techniques include descriptive analysis, instrument testing, classical assumption testing, multiple linear regression, and hypothesis testing, all conducted using SPSS version 26. The research findings indicate that both individual characteristics and OCB have a positive and significant effect, both partially and simultaneously, on employee performance at PT Bumi Siak Pusako. The discussion reveals that enhancing individual characteristics and OCB can support the achievement of better employee performance. The conclusion of this study is that both independent variables, individual characteristics and OCB, jointly contribute significantly to improving employee performance in the company.